Assessment of the use of livestock climate information in Senegal - Ouedraogo, Issa; Ndeye, Amy Kebe; Serign, Fall; Babacar, Seck (2025)
The assessment of use of the Livestock Climate Information Services (CIS) was done in four regions in Senegal to retrieve feedback from users to improve the delivery system. The survey revealed its significant impact on improving decision-making, reducing risks, and enhancing resilience among agro-pastoralists. The assessment Jokalante disseminated timely, actionable climate and agropastoral information through channels such as SMS, IVR, and community radio broadcasts. The services were widely adopted, with 90% of beneficiaries utilizing the information to optimize agricultural and livestock activities, safeguard resources, and mitigate losses. A notable 81% of respondents credited the information with preventing losses, while 99% expressed strong interest in continued access to these services, reflecting their perceived value. However, challenges such as message comprehension and financial sustainability were identified, underscoring the need for refinements in delivery methods and engagement strategies. Recommendations include enhancing communication accessibility, expanding dissemination channels, and fostering financial sustainability through collaborative models and targeted awareness campaigns. This assessment highlights the transformative potential of climate information services in fostering resilience, optimizing resource management, and supporting sustainable development in vulnerable pastoralist communities.